A Potential Indicator ARRDC2 Has Feasibility to Evaluate Prognosis and Immune Microenvironment in Ovarian Cancer - Zhang, Mengjun; Liu, Yunduo; Liu, Yuan; Hou, Siyu; Li, Hao; Ma, Ying; Wang, Can; Chen, Xiuwei (Frontiers in Genetics, 2022)
Background: The abnormal expression of α-arrestin protein family plays a key regulatory role in the occurrence and development of many cancers, including colorectal cancer and cervical cancer, and is inseparable from changes in the tumor immune microenvironment. However, the role of ARRDC2, an important member of this family, in the malignant biological process of ovarian cancer (OC) has not been reported, and its role in the change of the immune microenvironment is also unknown. Methods: In this study, HPA, TCGA, GEO and other databases were used to explore the role of ARRDC2 in the prognosis assessment of ovarian cancer. Then, GO, KEGG analysis and GSEA analysis of the biological processes and cell signaling pathways that ARRDC2 may be involved in activated or inhibited. In addition, the TIMER and TISIDB database were used to conduct in-depth research on the role of ARRDC2 in the change of the immune microenvironment of ovarian cancer. The CMap database explored and screened drugs that may be used for treatment. Through cell transfection, CCK-8, Ki-67 immunofluorescence, wound healing, transwell and clone formation assay, the effect of ARRDC2 knockdown on the malignant biological behavior of OC cells were explored. Results: There were significant differences between OC and ARRDC2 mRNA and protein levels. High ARRDC2 expression level is associated with poor overall survival and can be used as an independent prognostic factor. Interestingly, ARRDC2 expression is positively correlated with B cells, Neutrophils, Dendritic cells and CD8+ T cells, signifying that ARRDC2 may be related to infiltration of immune cells. ARRDC2 and its co-expressed genes are enriched in cell signaling pathways related to the immune system. We explored two possible drugs for the treatment of ovarian cancer. Finally, the results of in vitro experiments indicated that knockdown of ARRDC2 may inhibit malignant phenotypes such as proliferation and migration of OC cells. Conclusion: The differentially expressed ARRDC2 may be a potential prognostic indicator and can be used as a novel biomarker for exploring the immune microenvironment of ovarian cancer.